A case of primary aldosteronism combined with acquired nephrogenic diabetes insipidus - Kitae Kim; Jae Hyoung Lee; Sun Chul Kim; Dae Ryong Cha; Young Sun Kang (The Korean Society of Nephrology, 2014)
Aldosterone-producing adrenal adenoma can induce various clinical manifestations as a result of chronic exposure to aldosterone. We report a rare case of a 37-year-old man who complained of general weakness and polyuria. He was diagnosed with aldosterone-producing adrenal adenoma and nephrogenic diabetes insipidus. Aldosterone enhances the secretion of potassium in the collecting duct, which can lead to hypokalemia. By contrast, nephrogenic diabetes insipidus, which manifests as polyuria and polydipsia, can occur in several clinical conditions such as acquired tubular disease and those attributed to toxins and congenital causes. Among them, hypokalemia can also damage tubular structures in response to vasopressin. The patient's urine output was >3 L/d and was diluted. Owing to the ineffectiveness of vasopressin, we eventually made a diagnosis of nephrogenic diabetes insipidus. Laparoscopic adrenalectomy and intraoperative kidney biopsy were subsequently performed. The pathologic finding of kidney biopsy revealed a decrease in aquaporin-2 on immunohistochemical stain.